Effect of Variable Viscosity and Activation Energy on Convective Heat and Mass Transfer Flow of Nanofluid Past a Vertical Wavy with Thermal Radiation and Chemical Reaction in the Presence of Heat Generating Sources - Y. Madhusudhana Reddy (Mathematical Statistician and Engineering Applications, 2019)
We investigate effect of variable viscosity, activation energy on natural convective heat and mass transfer flow over a vertical wavy surface embedded in a fluid saturated porous medium with thermal radiation. The vertical wavy wall and the governing equations for flow heat ad mass transfer are transformed to a plane geometry case by employing the Runge-Kutta fourth order with Shooting technique. The non-dimensional velocity, temperature and nano-concentration graphs as well as skin friction, rate of heat and mass transfer coefficients are displayed for different values of variable viscosity, activation energy, radiation parameter, heat source parameter, chemical reaction and amplitude of the wavy surface. It is found that the increase in variable viscosity increases the velocities, reduces the temperature .The concentration reduces in the region adjacent to the wall and enhances far away from the wall, velocities, temperature and concentration experience enhancement with activation energy parameter.